The Psychological Impact of the COVID-19 Outbreak on Pregnancy and Mother-infant Prenatal Bonding - Tohme, Pia (2022)
This study aimed to assess the impact of the COVID-19 stress and anxiety on prenatal attachment during the second trimester of gestation. Pregnancy is an important stage for mothers-to-be in creating representations of themselves as a “mother”, with the developing attachment relationship to the unborn child considered as a milestone in the future parent’s developmental trajectory. The outbreak of the COVID-19 pandemic and the national health measures installed can hence have consequences on these representations and on prenatal attachment. Our sample consisted of 95 mothers that were recruited from a prenatal ultrasound screening center. Results suggested that the COVID-19 pandemic significantly affected prenatal attachment (PAI) with significant correlations between PAI total score and age, anxiety (DASS) and stress (IES-R). When entered in one model looking for predictors of PAI total score, age and COVID-19 stress were the only variables found to significantly predict prenatal attachment. We argue for a cultural component in explaining these results, hypothesizing that stress could trigger defensive strategies, leading to more investment in the attachment relationship, potentially playing the role of a protective factor.